2016
DOI: 10.1007/s10198-016-0783-4
|View full text |Cite
|
Sign up to set email alerts
|

Social/economic costs and health-related quality of life in patients with epidermolysis bullosa in Europe

Abstract: Background The aim of this study was to determine the social/economic costs and health-related quality of life (HRQOL) of patients with epidermolysis bullosa (EB) in eight EU member states. Methods We conducted a cross-sectional study of patients with EB from Bulgaria, France, Germany, Hungary, Italy, Spain, Sweden and the United Kingdom. Data on demographic characteristics, health resource utilisation, informal care, labour productivity losses, and HRQOL were collected from the questionnaires completed by pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 29 publications
3
69
0
9
Order By: Relevance
“…Rare diseases commonly place a large burden on family and caregivers, the impact of which is usually not taken into consideration in standard cost-effectiveness analyses (94)(95)(96). In light of the lack of appropriate HTA tools that can incorporate benefits and costs specific to rare disease treatments beyond the standard cost per QALY, e.g., socio-economic aspects, Multi-Criteria Decision Analysis (MCDA) is an approach that could be considered.…”
Section: Hta and Reimbursementmentioning
confidence: 99%
“…Rare diseases commonly place a large burden on family and caregivers, the impact of which is usually not taken into consideration in standard cost-effectiveness analyses (94)(95)(96). In light of the lack of appropriate HTA tools that can incorporate benefits and costs specific to rare disease treatments beyond the standard cost per QALY, e.g., socio-economic aspects, Multi-Criteria Decision Analysis (MCDA) is an approach that could be considered.…”
Section: Hta and Reimbursementmentioning
confidence: 99%
“…The estimated prevalence of EB in European Union countries is 2.4 cases per 100,000 inhabitants [29,30]. Angelis et al [31] estimated average annual costs per patient with EB that ranged between countries from €9509 to €49,233. Direct healthcare costs ranged from €419 to €10,688, direct non-healthcare costs ranged from €7449 to €37,451, and loss of labour productivity ranged from €0 to €7259.…”
mentioning
confidence: 99%
“…Therefore, it is not surprising to hypothesize that EB patients may develop a poor general quality of life associated with psychological impairment since childhood. Several studies have investigated this aspect and concluded that general quality of life in EB patients can be poor (Horn et al, 2002;Tabolli et al, 2009;Jeon et al, 2016;Angelis et al, 2016), but data on psychological aspects of EB have been conflicting. Some have reported no manifestation of anxiety and/or depressive symptoms (Fortuna et al, 2016) or other psychiatric disorders (Andreoli et al, 2002), whereas others have found a high prevalence of psychosocial problems and psychiatric symptoms (Margari et al, 2010).…”
Section: Discussionmentioning
confidence: 99%